2016
DOI: 10.1371/journal.pone.0165324
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Vitamin D Status and Metabolic Risk Factors among Korean Adults with Prediabetes

Abstract: Serum vitamin D status has been associated with prediabetes and metabolic syndrome. Evidence for the increased risk of metabolic disorders in individuals with prediabetes and a low vitamin D status is limited and uncertain. Furthermore, it has not been confirmed whether this possible relationship occurs in the Korean population. The aim of this study was to assess serum vitamin D status and to examine the relationship between serum vitamin D levels and metabolic risk factors in Korean adults with prediabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
(52 reference statements)
4
11
2
Order By: Relevance
“…Evidence from observational studies have pointed that the role of vitamin D status and metabolic risk factors with non-diabetic adults (24,25) or patients with dia-betes (26), which was assistance with our study among Chinese adults with PreDM. However, the previous study did not find the association between a low serum vitamin D status and central obesity among prediabetic Korean adults (27). In the current study, a significant inverse association was found between serum 25(OH)D3 levels and central obesity.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Evidence from observational studies have pointed that the role of vitamin D status and metabolic risk factors with non-diabetic adults (24,25) or patients with dia-betes (26), which was assistance with our study among Chinese adults with PreDM. However, the previous study did not find the association between a low serum vitamin D status and central obesity among prediabetic Korean adults (27). In the current study, a significant inverse association was found between serum 25(OH)D3 levels and central obesity.…”
Section: Discussioncontrasting
confidence: 80%
“…To our knowledge, there have been several studies reported the positive relationship between vitamin D deficiency and MS and its components among adults with non-diabetic adults (24,25) or patients with diabetes (26). Although there was only one study has examined the association between serum vitamin D levels and metabolic risk factors among adults with PreDM in Korean (27), the result could not be directly applied to a Chinese population due to ethnic differences in vitamin D metabolism and its nutritional status (28). Thus, we aimed to explore the nature and strength of the relationship between serum vitamin D status and metabolic risk factors among Chinese adults with PreDM.…”
mentioning
confidence: 99%
“…The data on vitamin D levels in patients with prediabetes compared to controls are inconsistent. Some studies show similar 25(OH)D levels in patients with prediabetes and controls and only hypovitaminosis D combined with high parathyroid hormone concentrations was associated with glycemic dysregulation in elderly patients [35], while others find lower levels of 25(OH)D in prediabetes vs. controls [36,37]. Vitamin D deficiency however seems to be related to insulin resistance in prediabetic patients [36,38], but not in normoglycemic subjects [39].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported an inverse association between plasma levels of vitamin D (vitD) and the risk of diabetes, insulin resistance and metabolic syndrome 4 7 . Clinical studies focused on type 2 diabetes (T2D), have shown a positive correlation between circulating vitD levels and insulin sensitivity, indicating that vitD deficiency may predispose to glucose intolerance, the secretion of altered insulin and T2D 8 10 , either through a direct action via activation of the vitamin D receptor (VDR), or indirectly through calcemic hormones and also through inflammatory processes 1 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%